Self-nanoemulsifying delivery of andrographolide: ameliorating islet beta cells and inhibiting adipocyte differentiation - Syukri, Yandi; Taher, Muhammad; Martien, Ronny; Lukitaningsih, Endang; Nugroho, Agung Endro; Zakaria, Zainul Amiruddin (Tabriz University of Medical Sciences, 2020)
Purpose: Insulin resistance is a characteristic of non-insulin-dependent diabetes mellitus associated with obesity and caused by the failure of pancreatic beta cells to secrete sufficient amount of insulin. Andrographolide (AND) improves beta-cell reconstruction and inhibits fat-cell formation. This research aimed to improve the delivery of water-insoluble AND in self-nanoemulsifying (ASNE) formulation, tested in streptozotocin (STZ)-induced diabetic rats and 3T3-L1 preadipocyte cells.